Interaction among BDI argumentative agents: a dialogue games approach - Rueda, Sonia Vivian (2005)
Negotiation is a fundamental activity in a multi-agent system. The members of the system negotiate in order to coordinate their activities and to distribute resources and tasks trying to reach a state acceptable to all. Carrying out a negotiation process requires that agents be able to interact. In this work, protocol interaction is implemented by means of dialogues between agents, and the set of dialogues generated inside the same negotiation process conforms a conversation. We propose an interaction language that allows argumentation-based negotiation among collaborative BDI agents. For the language description we use a formalism, called Dialogue Games, which allows to specify the nature of the utterances